Histórias em quadrinhos digitais para o ensino de ciências na formação de professores dos anos iniciais - Freitas, Karina Oliveira de (2015)
Although the need for the incorporation of Information and Communication Technologies (ICT) in teacher training processes are affirmed in public policies governing education in Brazil, studies have shown that undergraduate students are not being adequately prepared for the pedagogical use of ICT in their teaching practice. In this sense, the goal of this research was to contribute to the initial training of teachers who will work in the Initial Grades of Elementary School, in the context of science teaching through the production of digital educational materials (DEM) supported by an authoring tool of comics. The research, qualitative and quantitative character, fits as an action research, in which subjects were students of Bachelor of Education (Day) and Bachelor of Education (Night) from the Federal University of Santa Maria (UFSM) in the context of curriculum components Science and Education I and Science and Education II. The research consisted of three stages, involving exploratory study, implementation and evaluation of educational workshops for the production of strips using the ToonDoo Maker authoring tool and organization, analysis and evaluation of MED produced considering technical, pedagogical and cognitive aspects. The data were collected through questionnaires survey type. The results showed that the authoring process as a pedagogical strategy, the contact with different languages offered by comics and the support of authoring tool used, proved to be able to contribute to the enhancement of the pedagogical use of ICT in initial teacher training being prepared to work in science teaching in Initial Grades of Elementary School.